Principal Leadership and Teacher Job Satisfaction in Millennials and Z Generations: A Systematic Study (2015–2025) - Izza Mutia Raihan; Winda Dewi Listyasari (Journal of Educational Sciences, 2026)
This study is a systematic literature review that aims to explore the relationship between school leadership, organizational communication, and school culture to teacher job satisfaction, with a focus on millennials and Generation Z. A total of 22 studies from 76 initial articles (2015-2025) were analyzed using the PRISMA and VOSviewer methods. Bibliometric analysis using the PRISMA and VOSviewer methods identified 59 keywords grouped into five main themes. The findings showed that teacher job satisfaction (40 incidents) emerged as the most dominant theme with key factors including distributive and transformational leadership, teacher collaboration, and professional development. Organizational communication serves as an important mediator between leadership and teacher satisfaction. This research contributes to providing an integrative conceptual framework that bridges the leadership literature, organizational communication, and teacher generation dynamics, and offers practical implications for the development of school leadership models that are responsive to the needs of young teachers. The study emphasizes the importance of adaptive leadership, transparent internal communication, and supportive school cultures for teacher retention, performance, and motivation. Further research is recommended using longitudinal approaches and blended methods in a variety of school contexts.